Targeted dual-receptor phage cocktail against Cronobacter sakazakii: insights into phage-host interactions and resistance mechanisms - Kim, Seongok; Son, Bokyung; Kim, Yeran; Kim, Hyeongsoon; Nam, Gahyeon; Shin, Hakdong; Ryu, Sangryeol (Frontiers in Microbiology, 2024)
IntroductionCronobacter sakazakii is a notorious foodborne pathogen, frequently contaminating powdered infant formula and causing life-threatening diseases in infants. The escalating emergence of antibiotics-resistant mutants has led to increased interest in using bacteriophage as an alternative antimicrobial agent.MethodsTwo phages, CR8 and S13, were isolated from feces and soil samples and their morphology, physiology, and genomics were characterized. Phage receptor was determined using deletion mutants lacking flgK, rfaC, fhuA, btuB, lamb, or ompC genes, followed by complementation. Phage-resistant mutants were analyzed for phenotypic changes and fitness trade-offs using motility assays and Caco-2 cell invasion models.ResultsCR8 and S13 were identified as members of Caudoviricetes. Phage CR8 and phage S13 utilize flagella and LPS, respectively, to adhere to host cells. Bacterial challenge assay demonstrated delayed emergence of the resistant mutant as well as stronger lytic activity of a phage cocktail consisting of CR8 and S13 than the single phage treatment. Phenotypic analysis of the phage cocktail resistant strain, designated as CSR strain, revealed that the resistance resulted from the impaired receptor proteins for phage, such as defects in motility and alteration in LPS structure. CSR strain exhibited significant attenuation in invading human intestinal epithelial Caco-2 cells compared to WT cells.ConclusionThis study demonstrates that the development of the phage cocktail targeting distinct host receptors can serve as a promising antimicrobial strategy to effectively control C. sakazakii.